Strengthening relationship marketing model through antecedents and consequences of customer e-trust in e-commerce - Asakdiyah, Salamatun; Ismanto, Deny; Bonaga, Jason Keith (BISMA (Bisnis dan Manajemen), 2023)
E-commerce, or internet purchasing, has become more competitive as technology advances. This research aims to develop a relationship marketing model based on the causes and effects of e-trust among online shoppers. E-service quality and e-satisfaction are two factors that contribute to a company gaining their trust online. Meanwhile, e-commitment from customers follows on the heels of e-trust. Purposive sampling was used to choose 200 e-commerce users. This research used Partial Least Square (PLS) for data analysis. According to the findings, e-trust is affected by how satisfied and pleased clients are with the services they get online. E-service quality affects e-satisfaction, which in turn affects e-satisfaction and customers’ e-commitment. However, e-trust may also mediate the effects of e-service quality and e-satisfaction on e-commitment. E-satisfaction acts as a mediator between the effects of e-service quality on customers’ e-trust and e-commitment. These results show that customers’ e-trust is important in strengthening the influence of e-service quality and e-satisfaction on customers’ e-commitment. Likewise, e-satisfaction has an important role in strengthening the influence of e-service quality on e-trust and e-commitment. These findings prove that relationship marketing can be strengthened through the antecedents and consequences of customers’ e-trust to support and strengthen the achievement of e-commerce’s competitive advantage. Managers must create a strategy that integrates e-service quality, satisfaction, trust, and commitment to deliver a holistic customer experience. By prioritising these factors, managers can drive higher customer retention, loyalty, and ultimately, long-term business success in the online marketplace.